Students' Perceptions of the Flipped Classroom Approach for Learning Speaking Skills - Anwar, Choiril; Rohmawati, Isti (KnE Social Sciences, 2022)
The aim of this study was to describe students’ perceptions of the implementation of the flipped classroom approach for learning speaking skills. A descriptive qualitative research design was used. 23 tenth grade students of Madrasah Aliyah Nahdlatul ‘Ulama (MA NU) Mranggen in academic year 2020/2021 participated. The researchers collected the data through observations, questionnaires, and documentation analysis. According to the findings, the students felt that the flipped classroom approach was interesting and they could understand the method. The flipped classroom approach also increased interaction between the students and teacher, and improved students’ speaking skills. Keywords: flipped classroom, speaking skills